Improving services supply management in the defense sector: How the procurement process affects B2B service quality. Issue 2 (June 2015) - Hawkins, Timothy G.; Gravier, Michael J.; Berkowitz, David; Muir, William A.
Abstract Organizational buyers struggle with the effective management of business-to-business (B2B) services, yet little research has examined specifically how the procurement process impacts the supplier's level of delivered service quality. Based on a sample of 216 buyers of services, this study uses structural equation modeling to examine the relationships between service quality and its determinants. The results suggest that the sufficiency of the requirement definition and communication between the buyer and supplier are associated with B2B service quality, but that monitoring the supplier is not. Additionally, the internal customer's level of commitment to the procurement and the sufficiency of the allotted procurement lead time affect how sufficiently the buyer defines the requirement for the supplier. The internal customer's commitment also affects the amount of monitoring of and communication with the supplier. The study's findings have implications for integrating unified service theory with service-dominant logic; since service quality increases service value, these findings add fidelity to S-D Logic by unveiling specifically how to co-create value with the supplier. Two novel constructs are introduced to supply chain management discourse—sufficiency of the requirement definition and sufficiency of procurement lead time. Furthermore, a new measure of B2B service quality is offered. From these results, implications for practice and theory are drawn. The study concludes with a discussion of limitations and promising directions for future research.